Branching patterns emerge in a mathematical model of the dynamics of lung development. (9th December 2013) - Guo, Yina; Chen, Ting‐Hsuan; Zeng, Xingjuan; Warburton, David; Boström, Kristina I.; Ho, Chih‐Ming; Zhao, Xin; Garfinkel, Alan
Key points The development of the lung is a highly stereotypical process, including the structured deployment of three distinct modes of branching: first side branching and then tip splitting with and without 90° rotation of the branching plane. These modes are supposedly under genetic control, but it is not clear how genes could act to produce these spatial patterns. Here, we show that cascades of branching events emerge naturally; the branching cascade can be explained by a relatively simple mathematical model, whose equations model the reaction and diffusion of chemical morphogens. Our low‐dimensional model gives a qualitative understanding of how generic physiological mechanisms can produce branching phenomena, and how the system can switch from one branching pattern to another using low‐dimensional 'control knobs'. The model makes a number of experimental predictions, and explains several phenomena that have been observed but whose mechanisms were unknown.